A retrospective of the human viewpoint and its applicability to future systems. Issue 1 (16th October 2021) - Handley, Holly A. H.
Abstract: This paper describes the human viewpoint that was developed by a multinational panel of System Engineers and Human System Integration practitioners as an adjunct to existing systems architecting frameworks. The data collected in the human viewpoint enables engineering analyses that include human‐system trade‐offs to address stakeholder concerns. These analyses focus on the role definitions and task allocations that improve overall system performance. The human views method was developed to facilitate assessments of increasing fidelity, such as human data content analysis, human‐system design trade‐offs, restructuring role‐task allocations, and crew reductions due to automation. Ten examples, across a range of applications and levels of assessment, are provided to illustrate the ability to provide decision support to stakeholders. A reflection on the use of the human viewpoint traces its development across the examples, as well as suggesting a research agenda to improve its ability to address the design concerns of future systems.